2019
DOI: 10.1186/s13054-019-2508-4
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of intravenous sufentanil in critically ill patients supported with extracorporeal membrane oxygenation therapy

Abstract: Background Sufentanil is commonly used for analgesia and sedation during extracorporeal membrane oxygenation (ECMO). Both ECMO and the pathophysiological changes derived from critical illness have significant effects on the pharmacokinetics (PK) of drugs, yet reports of ECMO and sufentanil PK are scarce. Here, we aimed to develop a population PK model of sufentanil in ECMO patients and to suggest dosing recommendations. Methods This prospective cohort PK study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…19,21 Body temperature and total plasma protein level were found to be positively correlated with systemic clearance and peripheral volume of distribution of sufentanil. 26 Furthermore, Yang et al 27 showed that remifentanil volume and clearance were increased in adult patients who received VA-ECMO than those who did not receive ECMO. Remifentanil concentrations were affected by patient gender and pump speed of ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 Body temperature and total plasma protein level were found to be positively correlated with systemic clearance and peripheral volume of distribution of sufentanil. 26 Furthermore, Yang et al 27 showed that remifentanil volume and clearance were increased in adult patients who received VA-ECMO than those who did not receive ECMO. Remifentanil concentrations were affected by patient gender and pump speed of ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Median optimal sufentanil LD and MD were calculated based on observed PK data. To calculate the optimal doses, we used the range of 0.3–0.6 μg/L as the PK target for efficacious and safe analgesia [21], while higher levels have been described for anaesthetic effects in the literature [26]. Currently, the usual induction and maintenance doses of sufentanil are 0.25–2.0 and 0.5–1.5 μg/kg/h, respectively [11, 27-29].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal LD were calculated for each patient based on individual values of Vd c using the following formula: LD (μg/kg) = Vd (L/kg) × C ss (μg/L), where C ss is 0.45 μg/L as a midpoint of the sufentanil target steady-state therapeutic range (0.3–0.6 μg/L). Optimal daily MD were calculated for each patient based on individual values of CL using the following formula: MD (μg/kg/h) = CL (L/kg/h) × C ss (μg/L), where C ss is 0.45 μg/L as a midpoint of the sufentanil target steady-state therapeutic range (0.3–0.6 μg/L) [21].…”
Section: Methodsmentioning
confidence: 99%
“…Sufentanil has a strong affinity for opioid receptors, resulting in a more vigorous analgesic intensity and a longer duration of action than remifentanil. However, the metabolism of sufentanil is mainly dependent on liver blood flow 19,20 . Compared with sufentanil, a fast‐track protocol with a rapidly metabolized drug such as remifentanil may allow for better titration to keep patients within their therapeutic window and to minimize opioid‐induced side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the metabolism of sufentanil is mainly dependent on liver blood flow. 19,20 Compared with sufentanil, a fast-track protocol with a rapidly metabolized drug such as remifentanil may allow for better titration to keep patients within their therapeutic window and to minimize opioid-induced side effects. Our hospital adopted remifentanil-based fast-track anesthesia and reported on the relevant experiences.…”
Section: Discussionmentioning
confidence: 99%